Comparison of Sensitivity of Salmonella Typhi Bacteria Isolate Tifoid Fever Patients And Pure Culture To Some Antibiotics In Laboratory - Norma Farizah Fahmi; Lelly Aprilia Vidayati; Hamimmatus Zainiyah; Nailufar Firdaus (Universitas Andalas, 2019)
Typhoid fever is one of the infectious diseases which can cause many problems in Indonesia and other developing countries. This fever occurs as a result of infections triggered by Salmonella typhi bacteria. The growth of Salmonella typhi can be inhibited using antibiotics. This study aims at investigating whether there is a difference in the sensitivity test of Salmonella typhi bacteria in an isolate of patients with typhoid fever and pure culture in a laboratory on some antibiotics.Salmonella typhi bacteria were isolated typhoid fever suspects at one of the hospitals in Surakarta. Pure cultures of Salmonella typhi bacteria were obtained from Microbiological Laboratory of Setia Budi University. Sensitivity test of antibiotics on Salmonella typhi bacteria used diffusion method. Data on antibiotics of inhibition zone diameter (mm) of antibiotics were analyzed statistically using the Two-Way Anova test.The research results demonstrate that the sensitivity test on Salmonella typhi bacteria in an isolate of patients with typhoid fever shows resistance (R) towards amoxicillin and sensitivity (S) towards trimethoprim, chloramphenicol, gentamicin, ciprofloxacin. Meanwhile, pure culture shows sensitivity (S) towards trimethoprim, chloramphenicol, gentamicin, amoxicillin, ciprofloxacin. The diameter of the inhibition zone of the patient isolate is smaller than that of pure culture.